2016
DOI: 10.1089/ars.2016.6697
|View full text |Cite
|
Sign up to set email alerts
|

Protein Thiol Redox Signaling in Monocytes and Macrophages

Abstract: Significance: Monocyte and macrophage dysfunction plays a critical role in a wide range of inflammatory disease processes, including obesity, impaired wound healing diabetic complications, and atherosclerosis. Emerging evidence suggests that the earliest events in monocyte or macrophage dysregulation include elevated reactive oxygen species production, thiol modifications, and disruption of redox-sensitive signaling pathways. This review focuses on the current state of research in thiol redox signaling in mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 246 publications
(306 reference statements)
0
41
0
1
Order By: Relevance
“…It binds to other endogenous molecules forming, for example, the haemoglobin-glutathione complex, which serves as one of the markers of oxidative stress in human blood (7). With the advancement of detection methods in recent years (such as redox proteomic techniques and others), we have also learned about a vast number of interactions between glutathione and cellular proteins (8,9).…”
Section: F R O M T H E T O X I C O L O G I C a L P O I N T O F V I E mentioning
confidence: 99%
“…It binds to other endogenous molecules forming, for example, the haemoglobin-glutathione complex, which serves as one of the markers of oxidative stress in human blood (7). With the advancement of detection methods in recent years (such as redox proteomic techniques and others), we have also learned about a vast number of interactions between glutathione and cellular proteins (8,9).…”
Section: F R O M T H E T O X I C O L O G I C a L P O I N T O F V I E mentioning
confidence: 99%
“…We and others showed that maintaining protein thiol redox homeostasis is critical for the accurate programming and proper functioning of monocytes and macrophages [99, 103, 104]. Our data demonstrate that chronic exposure of monocytes to metabolic stress disrupts thiol redox homeostasis, resulting in monocyte dysfunction and the conversion of blood monocytes into a pro-inflammatory, pro-atherogenic phenotype, hyper-sensitive to chemoattractant [105, 106].…”
Section: Mkp-1 – Role In Monocytes and Macrophagesmentioning
confidence: 54%
“…Because the chemokine gradient we create in these mice is essentially unaffected by genetic, pharmacological, dietary or environmental exposure, changes in monocyte chemotactic activity actually reflect functional changes in these monocytes and, as we showed previously, also the reprogramming at both the protein and transcriptional level 17,20 . We reported that metabolic stress in mice increases monocyte responsiveness to chemoattractant and that this hyper-chemotactic activity correlates with increased protein S-glutathionylation, a reversible, redox-dependent posttranslational protein modification, which in most cases leads to loss of enzymatic and protein function 21,22 , and in some instances even promotes protein degradation 16,23 .…”
Section: Discussionmentioning
confidence: 99%